AIDS IN BRAZIL: DESCRIPTIVE ANALYSIS OF THE FREQUENCY AND DISTRIBUTION OF CASES FROM 2021 TO 2024 (CIPEEX, 2025)
Introduction: Acquired Immunodeficiency Syndrome (AIDS), caused by HIV, remains a major public health challenge in Brazil. Modes of transmission include unprotected sexual intercourse, blood transfusion, and vertical transmission, the latter being a particular concern for pregnant women. Furthermore, individuals with lower educational attainment are more vulnerable to infection, highlighting the need for prevention strategies tailored to social inequalities. Objective: To describe the frequency and distribution of AIDS cases in Brazil between 2021 and 2024, according to year of diagnosis, region, sex, educational level, and mode of transmission. Methods: This is a descriptive study based on consolidated data from SINAN/DATASUS up to June 30, 2024. All reported AIDS cases from 2021 to 2024 were included, stratified by year, region, sex, educational level, and mode of transmission (vertical transmission and transfusion). Results: During the study period, Brazil recorded 128,503 AIDS cases, with 71.1% in men and 28.8% in women. Regionally, the highest concentration occurred in the Southeast (36.6%), followed by the Northeast (24%), South (17.5%), North (13.4%), and Center-West (8.4%). A progressive increase was observed between 2021 and 2023, with a slight decline in 2024, likely due to partial data consolidation. Vertical transmission accounted for 830 cases, with 63% in men and 37% in women, predominantly in the Northeast (32.2%) and Southeast (25.9%). Cases due to blood transfusion were rare, totaling 9, mainly in the Southeast and South. Regarding educational level, the highest proportion of cases occurred among individuals with completed high school (34.6%), followed by those with incomplete 5th to 8th grade (14.4%) and completed higher education (12.9%). Among illiterate individuals, cases accounted for 2.3%. These findings demonstrate an association between lower educational attainment and greater vulnerability to HIV/AIDS infection. Conclusion: Between 2021 and 2024, AIDS cases in Brazil were concentrated in the Southeast and among men, with proportional increases in other regions. Detailed analysis by sex, region, educational level, and transmission mode highlights territorial and social inequalities, reinforcing the need for targeted strategies in prevention, testing, and antiretroviral treatment. Continuous monitoring of the different categories is essential to guide public health policies adapted to regional and sociodemographic specificities, contributing to the reduction of AIDS incidence and mortality in the country.
Keywords: Acquired Immunodeficiency Syndrome; Epidemiology; Public Health; HIV